Odpowiedź :
Odpowiedź:
a)
a₁ = 1
a₂ = a₁ + r = 4
a₃ = a₁ + 2r = 7
a₄ = a₁ + 3r = 10
a₂ * a₁ + r = 4
a₁ + r = 4
1 + r = 4
r - różnica ciągu = 4 - 1 = 3
a₆ = a₁ + 5r = 1 + 5 * 3 = 1 + 15 = 16
S₆ = (a₁ + a₆) * 6/2 = (1 + 16) * 3 = 17 * 3 = 51
b)
a₁ = 1/2
a₂ = 1
a₃ = 3/2
a₄ = 2
a₂ = a₁ + r = 1
a₁ + r = 1
1/2 + r = 1
r = 1 - 1/2 = 1/2
a₂₀ = a₁ + 19r = 1/2 * 19 * 1/2 = 1/2 + 19/2 = 20/2 = 10
S₂₀ = (a₁ + a₂₀) * 20/2 = (1/2 + 10) * 10 = 10/2 + 10 = 5 + 10 = 15
Wyjaśnienie:
Odpowiedź:
a)
a₁ = 1
a₂ = a₁ + r = 4
a₃ = a₁ + 2r = 7
a₄ = a₁ + 3r = 10
a₂ * a₁ + r = 4
a₁ + r = 4
1 + r = 4
r - różnica ciągu = 4 - 1 = 3
a₆ = a₁ + 5r = 1 + 5 * 3 = 1 + 15 = 16
S₆ = (a₁ + a₆) * 6/2 = (1 + 16) * 3 = 17 * 3 = 51
b)
a₁ = 1/2
a₂ = 1
a₃ = 3/2
a₄ = 2
a₂ = a₁ + r = 1
a₁ + r = 1
1/2 + r = 1
r = 1 - 1/2 = 1/2
a₂₀ = a₁ + 19r = 1/2 * 19 * 1/2 = 1/2 + 19/2 = 20/2 = 10
S₂₀ = (a₁ + a₂₀) * 20/2 = (1/2 + 10) * 10 = 10/2 + 10 = 5 + 10 = 15
Miałam to na lekcji :>